2022
DOI: 10.2478/jas-2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Genetic Characterization of Honey Bees (Apis mellifera L.) From Thrace Region of Turkey

Abstract: A detailed morphological and genetic characterization of honey bees from the Thrace and west Anatolian regions of Turkey was surveyed. A total of 1650 worker bee samples (110 colonies) were evaluated with the forty-one morphological characters and 217 honey bee samples were analyzed via DNA sequencing of the tRNAleu-cox2 region. In this study, three different populations, Thrace (Tekirdağ, Kırklareli and Edirne provinces), Island Gökçeada, and western Anatolia were formed based on morphometrics, since the Marm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Considering this geography, it was concluded that Anatolian (Apis mellifera anatoliaca Maa, 1953), Caucasian (Apis mellifera caucasica Gorbachev, 1916), Iranian (Apis mellifera meda Skorikov, 1929) and Syrian bees (Apis mellifera syriaca Buttel-Reepen, 1906) were found in Turkey. The existence of the fifth honey bee subspecies in the Thrace region according to morphological (Güler et al, 2010) and genetic marker studies was also reported (Smith et al, 1997;Palmer et al, 2000;Kekeçoğlu et al, 2007Kekeçoğlu et al, , 2009Özdil et al, 2009, 2022Ünal and Özdil, 2018).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Considering this geography, it was concluded that Anatolian (Apis mellifera anatoliaca Maa, 1953), Caucasian (Apis mellifera caucasica Gorbachev, 1916), Iranian (Apis mellifera meda Skorikov, 1929) and Syrian bees (Apis mellifera syriaca Buttel-Reepen, 1906) were found in Turkey. The existence of the fifth honey bee subspecies in the Thrace region according to morphological (Güler et al, 2010) and genetic marker studies was also reported (Smith et al, 1997;Palmer et al, 2000;Kekeçoğlu et al, 2007Kekeçoğlu et al, , 2009Özdil et al, 2009, 2022Ünal and Özdil, 2018).…”
Section: Introductionmentioning
confidence: 84%
“…Identification of the morphological and genetic variation in the honey bee subspecies and ecotypes, such as Thrace, Yığılca, Muğla, etc. ecotypes plays an important role in the formation of honey bee populations (Güler et al, 2010;Kekeçoğlu et al, 2007Kekeçoğlu et al, , 2009Özdil et al, 2009, 2022Güder et al, 2017;Gür et al, 2018;Ünal and Özdil, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of that study, old and new bee samples were clustered into two main clusters. It is important to protect honeybee ecotypes and genetic resources in their original regions [ 40 ], especially in order to determine the effects of commercial queen use and migratory beekeeping on the morphological variation [ 41 ]. In this study, besides determining the morphological characteristics of the Adıyaman honeybee, which has not been studied in detail before, the parameters of the colony performance were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Many molecular markers such as restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD) and mitochondrial DNA (mtDNA) analyses have been used in honey bee population genetics studies, but for the last 20 years, microsatellite loci have been quite widely used due to their features such as high polymorphism, multiallelicity, abundance in the genome and easy scorable (Kandemir & Kence, 1995;Smith et al, 1997;Bodur et al, 2007;Kekeçoğlu et al, 2009;Özdil et al, 2009;Liu et al, 2016;Rahimi et al, 2016;Haddad et al, 2018;Hassett et al, 2018;Yu et al, 2019;Özdil et al, 2022). Latterly, single nucleotide polymorphisms (SNPs) have been used in population genetics studies, however, thanks to the advantages provided by microsatellites, they could not get ahead of microsatellites even in the genomic era (Zimmerman et al, 2020;Mukherjee et al, 2022;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%